Analisis Keterbacaan Teks Buku Ajar Bahasa Indonesia SMA Kelas X Kurikulum Merdeka Menggunakan Formulasi Grafik Fry - Ai Siti Nurjamilah; Sri Maryani; Shinta Rosiana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
The readability of textbook texts is a crucial factor in learning effectiveness, particularly within the implementation of the Merdeka Curriculum, which emphasizes independent learning. This study analyzes the readability level of texts in Indonesian Language textbooks for Senior High School (SMA) Grade X under the Merdeka Curriculum using the Fry Graph Formula. A qualitative descriptive method was applied to 30 sample texts from three different textbooks used in schools across Tasikmalaya Regency, Tasikmalaya City, and Ciamis Regency. The results indicate that only 50% of the texts were appropriate for the Grade X level. Some texts were classified as too easy (suitable for elementary/lower junior high school levels), such as